Asset Recovery Mechanisms in Transnational Corruption Cases: Legal Frameworks and International Cooperation Challenges - Mayora Pranata, Feabo Adigo; Setiono, Joko; Fadri, Iza (Greenation Publisher & Yayasan Global Resarch National, 2025)
Asset recovery in transnational corruption cases has become an important issue in efforts to eradicate corruption crimes with cross-border impacts. The phenomenon of corruption, which is complex and organized in nature, often involves the concealment of assets in various jurisdictions, thus requiring a comprehensive legal mechanism and effective international cooperation. This research aims to analyze the legal framework for asset recovery both in Indonesia's national law and in the context of international instruments, as well as to evaluate the main challenges faced in its implementation. The approach method used is normative juridical by reviewing the latest legislation, such as Law Number 1 of 2023 on the Criminal Code, the Anti-Corruption Law, the Anti-Money Laundering Law, as well as international instruments such as the United Nations Convention against Corruption (UNCAC) and the recommendations of the Financial Action Task Force (FATF). The discussion covers the stages of asset recovery from identification, tracing, freezing, seizure, to the return of assets. It also discusses the role of related institutions such as the Corruption Eradication Commission (KPK), the Financial Transaction Reports and Analysis Center (PPATK), the Attorney General’s Office, the Police, and the Asset Recovery Center (PPA). The main obstacles identified include differences in legal systems between countries, slow mutual legal assistance procedures, lack of political will, and issues of transparency in the management of recovered assets. This research emphasizes that synergy between countries, legal harmonization, and strengthening of institutional accountability are the keys to the success of cross-border corruption asset recovery.